A Simple Technique to Improve Contractile Effect of Cold Plasma Jet on Acute Mouse Wound by Dropping Water. Issue 10 (30th March 2015) - Nasruddin,; Nakajima, Yukari; Mukai, Kanae; Komatsu, Emi; Rahayu, Heni Setyowati Esti; Nur, Muhammad; Ishijima, Tatsuo; Enomoto, Hiroshi; Uesugi, Yoshihiko; Sugama, Junko; Nakatani, Toshio
Abstract : A simple technique is tested to improve the contractile effect of a cold plasma jet on acute wounds of mice. Distilled water on the order of microliters is dropped onto wounds before treatment. To assess the fate of the water, an infrared thermal imager is applied. To evaluate the healing effect, macroscopic and immunohistological studies are conducted. Regarding the wound contractile effect, we show that combination treatment of plasma with dropped water seemed to have a greater effect than plasma treatment alone. Plasma may modify the wound surface through such water, chemically and physically. The histological stiffness of the wound surface during maturation and remodeling, however, may also influence the fate of the water during treatment. Abstract : A simple technique is tested to improve the contractile effect of plasma on wounds. Water is dropped on wounds before treatment. To evaluate its effect, macroscopic and microscopic studies are performed. We show that combination treatment of plasma with water appeared to promote the wound contractile effect compared with plasma alone. Plasma may modify wounds via water, chemically and physically.